IoT-Based Automated and Contactless Shopping Cart - Mr.Gurpreet Singh, Mr.Jaswinder Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
People's lives have been enriched by cutting-edge technologies. In general retailers, there has been a growing interest in risk and simple instalments of bills. We all desire high quality in whatever we use in our day-to-day lives. The assignment depicts how to create a robotized and efficient framework for the retail industry that would make purchasing more convenient, client-friendly, and secure. As a result, large crowds have formed in shopping centres, resulting in long lines at the charging counter, as the clerk must sift each item before entering it into the charging record. The whole billing structure is a little cumbersome. As a result, we came up with the idea of creating a mending electronic device to make up for lost time with this problem. It's referred to as a "programmed shopping cart." This is dependent on a Raspberry Pi with an LCD and QR scanner, as well as a Bluetooth control. The remote system uses a 16x2 LCD and Bluetooth modules to function successfully within a defined range. The one that guides the ease, consolation, and efficiency in typical everyday presence is an innovative thing with societal affirmation. The QR scanner examines the item's one-of-a-kind code and cost at the point where you choose an item and deposit it into the cart. Furthermore, it is displayed on the LCD screen, so once the customer has finished shopping, he or she must proceed to the counter and pay the amount as displayed on the LCD screen mounted on the trolley. This will save the time that was previously spent checking everything.